Lysophosphatidylethanolamine improves diastolic dysfunction by alleviating mitochondrial injury in the aging heart - Guiwen Xu; Wei Xiao; Pengqi Sun; Yuanjun Sun; Xinyu Yang; Xiaomeng Yin; Yang Liu (Journal of Lipid Research)
Diastolic dysfunction in aging mice is linked to mitochondrial abnormalities, including mitochondrial morphology disorders and decreases in membrane potential. Studies also show that aberrant mitochondrial lipid metabolism impairs mitochondrial function in aging cardiomyocytes. Our lipidomic analysis revealed that phosphatidylethanolamine (PE) levels were significantly decreased in aging myocardial mitochondria. Here, we investigated whether a reduction in PE levels in myocardial mitochondria contributes to mitochondrial injury as well as HFpEF pathogenesis and whether modulation of PE levels could ameliorate aging-induced HFpEF. Echocardiography was used to assess cardiac diastolic function in adult and aging mice treated with lysophosphatidylethanolamine (LPE) or saline. Mitochondrial morphologies from tissue samples were evaluated by transmission electron microscopy (TEM), while mitochondrial membrane potential and reactive oxygen species (ROS) levels were assessed using JC-1, MitoSOX, and DCFH-DA detection assays. We performed GO enrichment analysis between adult and aging mice and discovered significant enrichment in transcriptional programs associated with mitochondria and lipid metabolism. Also, mitochondrial PE levels were significantly decreased in aging cardiomyocytes. Treatment with LPE (200 μg/kg) significantly enhanced PE content in aging mice and improved the structure of mitochondria in cardiac cells. Also, LPE treatment protects against aging-induced deterioration of mitochondrial injury, as evidenced by increased mitochondrial membrane potential and decreased mitochondrial ROS. Furthermore, treatment with LPE alleviated severe diastolic dysfunction in aging mice. Taken together, our results suggest that LPE treatment enhances PE levels in mitochondria and ameliorates aging-induced diastolic dysfunction in mice through a mechanism involving improved mitochondrial structure and function.